2014
DOI: 10.1186/2049-3258-72-45
|View full text |Cite
|
Sign up to set email alerts
|

Sarcopenia: burden and challenges for public health

Abstract: Sarcopenia, operationally defined as the loss of muscle mass and muscle function, is a major health condition associated with ageing, and contributes to many components of public health at both the patient and the societal levels. Currently, no consensual definition of sarcopenia exists and therefore it is still a challenge to establish the actual prevalence of sarcopenia or to establish the direct and indirect impacts of sarcopenia on public health. Anyway, this geriatric syndrome represents a huge potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
286
1
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 357 publications
(303 citation statements)
references
References 59 publications
5
286
1
11
Order By: Relevance
“…The prevalence of sarcopenia is higher in men and increases with age [19] as reported in our study. Statistically significant differences were maintained in all measurements relative to sarcopenia by gender.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…The prevalence of sarcopenia is higher in men and increases with age [19] as reported in our study. Statistically significant differences were maintained in all measurements relative to sarcopenia by gender.…”
Section: Discussionsupporting
confidence: 75%
“…In our study it was observed that among persons aged 70 years and older the prevalence was 16.2% (15.1% in women and 18.2% in men). The differences in the prevalence reported in the literature with our results appear to be attributed to the age of the population and to the methods used for the evaluation as well as cut-off points used for the diagnosis of sarcopenia [19]. Though, previous studies, remark the special value of comparison of elderly population with the subjects under similar characteristics, to reflect with precision the trend of sarcopenia prevalence [20][21][22][23].…”
Section: Discussioncontrasting
confidence: 45%
See 2 more Smart Citations
“…1 World Health Organization (WHO) memprediksikan pada tahun 2050 setidaknya terdapat 2 milyar orang berusia 65 tahun ke atas dibandingkan dengan 600 juta pada saat ini. 1,2 Lansia mengalami proses degeneratif yang berlangsung secara progresif, dengan salah satu manifestasinya berupa penurunan massa otot pada lansia. Proses terjadinya penurunan massa otot melibatkan interaksi sistem saraf tepi dan sentral, hormonal, status nutrisi, imunologis, dan aktivitas fisik yang kurang.…”
Section: Pendahuluanunclassified